Upaya Peningkatan Kompetensi Manajerial Mahasiswa di Lingkungan Perguruan Tinggi Islam Berbasis Pesantren - Ariyanti, Novi (Tarbiyatuna: Jurnal Pendidikan Ilmiah, 2025)
Amidst the urgency of producing adaptive and competent graduates in the era of globalization, this study examines the implementation of managerial practicum integrated with Islamic values in pesantren-based Islamic Higher Education, an area still underexplored in the literature. Therefore, this research aims to explore the strategies and contributions of the Islamic Education Management Practicum (PMPI-II) program in enhancing students' managerial competencies within this environment. The research employs a qualitative case study approach. Data collection involves in-depth interviews, participant observation (with the researcher acting as Field Supervising Lecturer - DPL), and documentation study. Data analysis follows the Miles, Huberman, and Saldana model. The study's findings reveal four main strategies of PMPI-II: needs identification & program planning, implementation, active coordination & communication, and periodic monitoring & evaluation. These strategies demonstrate alignment with principles of program management, strategic planning, and Stakeholder Theory. PMPI-II significantly contributes to improving students' planning skills, administrative task execution, communication, and coordination. Through experiential learning, the program also fosters an Islamic professional character, encourages adaptation to pondok culture, and instills the values of ta'dzim (respect) and musyawarah (deliberation). Consequently, PMPI-II emerges as an effective model for value-based managerial competence development in the pesantren environment.